Effect of Different Saudi Honey Types Mixed with Natural Substances on Some Bacterial Strains - Fatimah A. Nashawi,; Hani Y. Abdullah,; Nahlaa A. Khalifa,; Ibrahim A. Alzahrani,; Ahmed A. Al-Ghamdi, (Journal of King Abdulaziz University: Medical Sciences, 2023)
To evaluate the antibacterial eff ects of three types of Saudi honey (Feghra, Sider and Natural honey) alone and mixed with ginger or lemon in comparison to Manuka honey as a potential natural antibacterial agent. Saudi honeys were evaluated against five types of bacterial strains; Klebsiella pneumoniae, Staphylococcus aureus, Pseudomonas aeruginosa, Haemophilus influenzae and Streptococcus pneumoniae. Chocolate agars were prepared first with different concentrations of each type of honey, and then with specific concentrations either of ginger or lemon added to honey. Bacterial species were inoculated on each agar and incubated at 37oC in a CO2 incubator overnight. Significant differences were found between diff erent types of honey and different concentrations of the same honey on bacterial growth. There are no significant differences and synergistic effects when adding ginger to diff erent honey types. Addition of lemon show significant differences and good synergistic effects against all tested bacterial species except Klebsiella pneumoniae and Staphylococcus aureus at 15 and 20% honey concentration. In conclusion, antibacterial effects of different types of honey are type and concentration dependent. Adding lemon to the different types of honey changes the pH and acidity and increases the honey’s antibacterial effect.